Fecundity and Seed Dormancy Variation Within and Among Echinochloa Species - Tahir, Hussain; Roma-Burgos, Nilda (Frontiers in Agronomy, 2021)
The Echinochloa genus contains two of the world’s top five worst weeds. The persistence and 16 weediness of Echinochloa spp. are partly due to its seed longevity and variable seed dormancy. 17 In the USA, specifically in Arkansas, multiple species infest the same field in many cases. 18 Persistence could vary across species and dormancy affects infestation level. Studies were 19 conducted to evaluate the seed production potential and dormancy of Echinochloa species in the 20 State. Ninety-four accessions were characterized in a common garden in Fayetteville, Arkansas, 21 USA. The species were Echinochloa colona (L.) Link, E. crus-galli (L.) P. Beauv, E. muricata P. 22 Beauv and E. walteri (Pursh). Only one accession was identified as E. walteri and was excluded 23 from data analysis. Seeds were after-ripened for six months at room temperature and germinated 24 at 32 °C day/ 23 °C night with 12-h daylength. Germination was monitored for 14 d. The 25 Echinochloa species in Arkansas were predominantly E. colona (78%). E. colona had the highest 26 seed production and the lowest seed dormancy among species. Dormancy within each species 27 varied greatly, especially for E. colona, with a germination capacity (GC) of 41-99%. Only 2.7% 28 of 73 E. colona accessions were dormant. E. crus-galli had 56-79% GC; 33% of the accessions 29 were dormant. E. muricata had 2-39% germination, with all accessions considered dormant. E. 30 colona had the highest fecundity, with 72,973 seeds per plant. This was 2.3- and 2.6x higher than 31 that of E. crus-galli and E. muricata, respectively. High seed production and high germination 32 capacity must have contributed to the dominance of E. colona among other Echinochloa species. 33 E. muricata is expected to persist longer in the soil seedbank compared to E. colona and E. crus-34 galli. Seed production, dormancy and longevity will affect interspecies population dynamics in 35 response to management tactics.